Performance of Decentralized Local Service Delivery in Developed Countries: Case Study of Japan - Mudalige, Priyantha W. (European Scientific Journal, ESJ, 2020)
Many countries decentralize the administrative, fiscal, and political functions of the central government to lower-level governments. In many developing and developed countries, governments and their policymakers have used decentralization as a means of improving the delivery of local service. Accordingly, this study is based on the delivery of local services to the people by the local governments of Japan as a developed country. The overall objective of this article is to review the performance of decentralized local service delivery in developed countries and based on a case study of Japan. The study also aims to examine the correlation between the revenue and expenditure of local governments of Japan and its trends. Basically, this article has been written based on secondary data materials. This data consists of qualitative and quantitative characteristics. Hence, a qualitative and quantitative descriptive method has been applied to analyse the performance of local government decentralization in Japan, and descriptive statistical methods are used to analyse the data and the correlation between revenue and expenditure. The problem in this research is how the functional political institutions created for local service delivery at the sub-national governments in Japan affects the success of decentralization. This research revealed several findings. The local governments of Japan have a sound institutional system and several powers recognized by the constitution. Japanese local governments monitor over 70% of national works, but a majority of the standard public services are the responsibility of local governments. Karl Pearson’s correlation value of revenue and expenditure is 0.979, and there is a strong positive relationship between revenues and expenditure. In Japan, the highest value of local government spending is on public welfare. It is followed by education, civil engineering works, and general administration, second, third, and fourth, respectively. Also, its central and local administrative institutions are maintained in a mutually dependent and mutually complementary relationship. Most of the local governments are collaborating with the private sector in Japan. As a result, the efficiency of service delivery has improved at the local level. In this way, waste management, which is a major local problem in Japan, is being dealt with closely by the central government and the local governments.